Mathematics Problem Solving Skill Reviewed from Cognitive Style on Problem Based Learning with Aceh Custom Nuances with Descriptive Feedback - Safitri, Friantiani; Kartono, Kartono; Mastur, Zaenuri (Unnes Journal of Mathematics Education Research, 2021)
Problem solving skill is the core of mathematics lesson. This research aims to describe mathematics problem solving skill reviewed from cognitive style based on independent and dependent field categories. It was done for X graders of Public SHS 1 Samudera in academic year 2018/2019. This mixed method research used sequential explanatory strategy. It is a procedure to collect quantitative and qualitative data orderly. The technique of collecting quantitative data was done by problem solving skill test while the qualitative data was done by documentation, questionnaire, and interview. The results showed that mathematics problem solving skill of the students on each cognitive category had different mastery indicators. The differences did not depend on cognitive style categories of the students but based on learning activity.